Effect of ISBAR Communication Mode on the Bedside Delivery Quality of Nurses Working in the Department of Rheumatology and Immunology - Wang M; Gao Z (Journal of Multidisciplinary Healthcare)
Meiyu Wang, Zhenlei Gao Department of Rheumatology and Immunology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of ChinaCorrespondence: Zhenlei Gao, Department of Rheumatology and Immunology, Beijing Chao-Yang Hospital, Capital Medical University, 8 Gong-Ti South Road, Beijing, 100020, People’s Republic of China, Tel +86-10-85231063, Email gaozhenleii1@163.comObjective: To explore the effect of ISBAR communication mode on the quality of bedside handover in the rheumatology and immunology department.Methods: Nine nurses in the ward were prospectively selected using convenience sampling, and the nursing handover scale (NHS), the nurse “eleven knows” of patient condition assessment scale, and medical staff satisfaction questionnaire on morning nursing handover were collected and compared 1 month before the implementation of the ISBAR handover mode (ie, Apr. 1, 2024) and 1 month after the implementation of the mode for three months (ie, Sept.1, 2024).Results: The scores of all items in the NHS, the knowledge of the nurse “eleven knows” of patient condition, and both doctor’s and nurse’s satisfaction with morning nursing handover report were increased, and the writing and reporting time required for nursing handover report was decreased after the implementation of the ISBAR communication mode compared with those before the use of this mode.Conclusion: The ISBAR communication mode effectively improves the quality of bedside handover in rheumatology department, enhances the nursing handover assessment, helps nurses to understand the patients’ condition, and standardizes the nurse handover process.Keywords: ISBAR communication mode, bedside handover, rheumatology and immunology department, nursing